Density-dependent regulation of body mass and condition in badgers (Meles meles) from Wytham Woods - Macdonald, D; Newman, C; Stewart, P; Domingo-Roura, X; Johnson, P (2002)
Body mass and an index of condition for badgers (Meles meles) in a highdensity population (Wytham Woods, UK) were examined between 1990 and 1997 and compared with the size of the groups with which individuals were associated. Both body mass and condition decreased as centered group size increased. Fecundity also declined with increasing centered group size. Female badgers exhibited the greatest effects of density-dependent constraints on body mass and condition in autumn, whereas for males the effect was most pronounced in spring.